Minat Investasi Saham Generasi Z Kota Tasikmalaya (Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Perjuangan Tasikmalaya) - Susanti; Rita Tri Yusnita; Gian Riksa Wibawa (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study is one way that can be done to find out how Investment Knowledge, Risk Perception and Return influence Stock Investment Interest (Study on Students of the Faculty of Economics and Business, University of Perjuangan Tasikmalaya). The method used is a quantitative method with a survey approach. The population in this study were Generation Z students of the Faculty of Economics and Business, University of Perjuangan Tasikmalaya who were still active in 2020-2023 and with a reference year of birth from 1995-2010 (minimum age 17 years). With a research sample of 100 respondents. This sampling technique uses the Proportionate Stratified Random Sampling technique. The data obtained are primary data and secondary data. The analysis tool used is Multiple Linear Regression using SPSS Version 25. The results of the analysis show that Investment Knowledge, Risk Perception and Return simultaneously have a significant effect on Stock Investment Interest. Risk Perception and Return partially have a significant effect on Stock Investment Interest. While Investment Knowledge partially does not have a significant effect on Stock Investment Interest.